Mahasiswa Kesejahteraan Sosial FISIP USU Mewujudkan Bebas Bullying dan Membangun Sosialisasi yang Kuat di Panti Asuhan Ar-Rahman - Damaiyanti S, Berli Sela; Ritonga, Fajar Utama; B, Bengkel (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The author conducted practicum I at the Ar-Rahman Orphanage. The first practicum conducted by the author was to research the problems experienced by the orphanage children. The problems experienced by the orphanage children were the lack of a culture of socializing so that they had difficulty in learning in groups. This condition, which is exacerbated by the tendency of today’s children to be alone rather than interact, creates difficulties in group learning and has the potential to hinder their development. Seeing the urgency of this problem, the author was motivated to conduct a mini project with the main goal of increasing children’s interest in socializing, which is expected to have an impact on increasing their self-confidence. The clients who are the focus of this project are children from various levels of education, from Elementary School (SD) to Vocational High School (SMK). In this study, the author used a comprehensive social casework approach, from the preparation stage to termination. The Ecomap method and focus group discussions (FGD) were chosen to collect data and understand the existing social dynamics. After going through all these stages, the expected result is that the orphanage children can return to cultivating healthy social interactions. Thus, they will not only be more adaptable in learning at school, but also able to create an environment free from bullying behavior. This project is expected to be an important foundation for the development of essential life skills for the future of orphanage children.